2014
DOI: 10.3138/ptc.2012-59
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Effect of Exercise Training in People with End-Stage Renal Disease on Hemodialysis: A Systematic Review with Meta-analysis

Abstract: Purpose: The primary purpose of this systematic review was to evaluate the anabolic effect of exercise intervention in adults with end-stage renal disease on hemodialysis (HD). The secondary objectives were to evaluate the influences of participant characteristics and exercise parameters on changes in muscle size. Methods: Electronic databases (Cochrane, CINAHL, EMBASE, PEDro, PubMed and SCOPUS) were searched from inception to November 2012. Randomized clinical trials published in English that included adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…Two [ 46 , 47 ] of the six case-control studies evaluating the effect of exercise established a significant increment in GS. These findings are in alignment with what has been reported in the literature [ 52 , 53 ]. However, adherence and uptake of these exercises is limited [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Two [ 46 , 47 ] of the six case-control studies evaluating the effect of exercise established a significant increment in GS. These findings are in alignment with what has been reported in the literature [ 52 , 53 ]. However, adherence and uptake of these exercises is limited [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that strengthening exercise is an anabolic intervention to increase muscle mass, either during dialysis sessions (intradialytic) or on nondialysis days (Sawant et al . ). To the best of our knowledge, meta‐analyses have not been performed to determine the concomitant effect of intradialytic exercise on the physical function, depression and quality of life for haemodialysis patients.…”
Section: Introductionmentioning
confidence: 97%
“…However, the presumed benefits of exercise in this population have not been observed consistently in interventional studies (Sawant et al. ).…”
Section: Introductionmentioning
confidence: 93%